Individual pharmacokinetic variation leads to underdosing of ciprofloxacin in some cystic fibrosis patients. Issue 3 (4th November 2016) - Schultz, A.N.Ø.; Høiby, N.; Nielsen, X.C.; Pressler, T.; Dalhoff, K.; Duno, M.; Buchard, A.; Johansen, H.K.; Wang, H.; Dalbøge, C.S.
Summary: Background: Ciprofloxacin (CIP) is frequently used when treating cystic fibrose (CF) patients with intermittent Pseudomonas aeruginosa (P. aeruginosa) lung colonization. However, approximately 20% of the patients progress to chronic infection despite early intervention. The aim of this study, was to investigate the pharmacokinetics of CIP, to evaluate if CYP3A4‐related metabolism is involved and to find the optimal dose needed to eradicate intermittently colonizing bacteria in the lungs of CF patients. Methods An open‐label, prospective pharmacokinetic study was performed. Twenty‐two adult CF‐patients were each given 500 mg CIP orally. One blood sample was taken at t  = 0, and the following 12 hr, nine blood samples were collected. The optimal dose and interval was then calculated by Monte Carlo simulation. CYP3A4‐activity was mesured using the Erythromycin Breath Test (ERMBT). Results A 14‐fold variation in AUC for the 500 mg CIP (median 473.5 µg/ml × min), and a 30‐fold variation in Cmax for CIP (median 2 µg/ml) was found. For CYP3A4‐activity the variation was 8‐fold. No correlation was found between the CYP3A4‐activity and CIP‐concentrations. The probability of eradicating intermittent P. aeruginosa colonization in the lungs of CF patients was found to be 57% (3 doses/day), when 500 mg CIP was given. It was calculated to be 89% (2 doses/day) and 94% (3 doses/day), respectivly if 750 mg CIP had been given. Conclusion A large pharmacokinetic difference of CIP in CF patiens was found, not explained by CYP3A4 variation. CIP should be given at 750 mg two or three times daily to adult CF patients with intermittently colonization.Pediatr Pulmonol. 2017;52:319–323. © 2016 Wiley Periodicals, Inc.